Ketidakadilan Gender Terhadap Tokoh Perempuan dalam Novel 9 Matahari karangan Adenita: Sebuah Kajian Feminisme - Guntar, Elsita Lisnawati; Veri Kusumaningrum, Ni Ketut; Jetia Moon, Yuliana (Humanis; Vol 27 No 4 (2023), 2023)
This research is motivated by the assumption that women only play a role in the domestic field and do not have the rights and freedoms to study, act, and associate. This research aims to determine the forms of gender injustice towards female characters in the novel 9 Matahari by Adenita and the rebellion efforts made by female characters against this injustice. The theory used is feminist theory. This research uses qualitative data in the form of documents. Data collection in this research used the library method (library research), namely library sources in the form of books, articles, journals and other literature. Based on the results of the analysis, it was found that this novel tells the role of the main character, who is female, and all the life around her. This main character not only fights for education but also a decent life for women. This novel contains an idea as well as a rebellion that women must get a proper education to improve their future, and the main character in this novel is able to make it happen.